Self-compassion explains substantially more variance in eating disorder psychopathology and associated impairment than mindfulness. (March 2021) - Messer, Mariel; Anderson, Cleo; Linardon, Jake
Highlights: Explored the amount of variance explained by mindfulness and self-compassion on eating disorder pathology and impairment. Self-compassion and mindfulness were lowest in bulimia nervosa, followed by binge-eating disorder and control participants. Self-compassion explained between 13–25 % more variance than mindfulness on ED psychopathology and associated impairment. Pattern of results remained the same across different symptom profiles. Self-compassion may be a better intervention target than mindfulness, particularly for at risk groups or people with a clinically significant ED. Abstract: This study aimed to (1) examine the unique role of mindfulness and self-compassion on eating disorder (ED) psychopathology and functional impairment, and (2) compare levels of mindfulness and self-compassion between health controls and individuals categorized with bulimia nervosa (BN), and binge-eating disorder (BED). Data were analyzed from 1101 community-based participants, of which 145 met criteria for BN, 150 for BED, and 286 for healthy controls. Results from a series of multiple regressions revealed that self-compassion accounted for substantially more variance in ED psychopathology and functional impairment than mindfulness in the total sample and across the three subgroups, at times explaining 20 times more variance than mindfulness. Results remained unchanged when excluding the mindfulness subscale from the Self-Compassion Scale. When comparing these variables across the three study groups, results showed that self-compassion and mindfulness levels were lowest in the BN group, followed by the BED group, and then the healthy control group. Findings overall suggest that non-judgmental awareness may be less important in explaining levels of ED psychopathology than the nature of one's interaction with emotionally charged, negative experiences. Findings also point to possible priority intervention targets in indicated prevention and treatment programs.